Definition of culture conditions for Arxula adeninivorans, a rational basis for studying heterologous gene expression in this dimorphic yeast. (1st June 2014) - Stöckmann, Christoph; Palmen, Thomas G; Schroer, Kirsten; Kunze, Gotthard; Gellissen, Gerd; Büchs, Jochen
Abstract: The yeast Arxula adeninivorans is considered to be a promising producer of recombinant proteins. However, growth characteristics are poorly investigated and no industrial process has been established yet. Though of vital interest for strain screening and production processes, rationally defined culture conditions remain to be developed. A cultivation system was evolved based on targeted sampling and mathematical analysis of rationally designed small-scale cultivations in shake flasks. The oxygen and carbon dioxide transfer rates were analyzed as conclusive online parameters. Oxygen limitation extended cultivation and led to ethanol formation in cultures supplied with glucose. Cultures were inhibited at pH-values below 2.8. The phosphorus demand was determined as 1.55 g phosphorus per 100 g cell dry weight. Synthetic SYN6 medium with 20 g glucose l −1 was optimized for cultivation in shake flasks by buffering at pH 6.4 with 140 mmol MES l −1 . Optimized SYN6 medium and operating conditions provided non-limited cultivations without by-product formation. A maximal specific growth rate of 0.32 h −1 and short fermentations of 15 h were achieved. A pH optimum curve was derived from the oxygen transfer rates of differently buffered cultures, showing maximal growth between pH 2.8 and 6.5. Furthermore, it was shown that the applied medium and cultivation conditions were also suitable for non-limiting growth and product formation of a genetically modified A. adeninivorans strain expressing a heterologous phytase.